AUTONOMOUS CONCEPTS OF THE CASE-LAW OF THE EUROPEAN COURT OF HUMAN RIGHTS AND OF THE COURT OF JUSTICE OF THE EUROPEAN UNION IN MATTERS OF DISCIPLINARY, ADMINISTRATIVE, FINANCIAL AND CRIMINAL LIABILITY - Gheorghe BOCSAN (Challenges of the Knowledge Society)
Often, the delimitation between criminal law per se and other branches of public law involving the application of sanctions by the authorities of the Member States or by the institutions, bodies, offices and agencies of the European Union is difficult to operate. From the point of view of the guarantees of the fair trial, as they are regulated by art. 47 of the Charter of Fundamental Rights of the European Union and art. 6 of the Council of Europe Convention for the Protection of Fundamental Rights and Freedoms, both the ECJ and the ECHR have developed, through continuous and elaborated jurisprudence, autonomous concepts on the basic notions by which aforementioned guarantees operate: “criminal charges”, “criminal proceedings “,” criminal sanction “,” court “,” court with jurisdiction in criminal matters “etc. The present study analyses the mechanisms of the influence exercised by the autonomous concepts developed in the ECHR case-law on the mentioned legal topic on the legal acts of the Union, but also the uniform meanings resulting from the corroboration of these autonomous concepts with those of the ECJ jurisprudence in the same field. Starting from some basic concepts of ECHR jurisprudence on the notion of criminal offence, synthesized in the Engel Criteria and many subsequent cases, such as Bendenoun v. France, Jussila v. Finland, Ezeh and Commons v. United Kingdom, the issue of the delimitation we have referred to above acquires contours in the case-law of ECJ in relevant cases such as Bonda, Baláž or Hans Åkerberg Fransson.